A Penicillium chrysogenum-based expression system for the production of small, cysteine-rich antifungal proteins for structural and functional analyses. Issue 1 (December 2016) - Sonderegger, Christoph; Galgóczy, László; Garrigues, Sandra; Fizil, Ádám; Borics, Attila; Manzanares, Paloma; Hegedüs, Nikoletta; Huber, Anna; Marcos, Jose; Batta, Gyula; Marx, Florentine
Abstract Background Small, cysteine-rich and cationic antifungal proteins (APs) from filamentous ascomycetes, such as NFAP fromNeosartorya fischeri and PAF fromPenicillium chrysogenum, are promising candidates for novel drug development. A prerequisite for their application is a detailed knowledge about their structure–function relation and mode of action, which would allow protein modelling to enhance their toxicity and specificity. Technologies for structure analyses, such as electronic circular dichroism (ECD) or NMR spectroscopy, require highly purified samples and in case of NMR milligrams of uniformly15 N-/13 C-isotope labelled protein. To meet these requirements, we developed aP. chrysogenum -based expression system that ensures sufficient amount and optimal purity of APs for structural and functional analyses. Results The APs PAF, PAF mutants and NFAP were expressed in aP. chrysogenum ∆paf mutant strain that served as perfect microbial expression factory. This strain lacks thepaf -gene coding for the endogenous antifungal PAF and is resistant towards several APs from other ascomycetes. The expression of the recombinant proteins was under the regulation of the strongpaf promoter, and the presence of apaf -specific pre-pro sequence warranted the secretion of processed proteins into the supernatant. The use of defined minimal medium allowed a single-step purification of the recombinant proteins. The expression system could be extended to express PAF in the related fungusPenicillium digitatum, which does not produce detectable amounts of APs, demonstrating the versatility of the approach. The molecular masses, folded structures and antifungal activity of the recombinant proteins were analysed by ESI–MS, ECD and NMR spectroscopy and growth inhibition assays. Conclusion This study demonstrates the implementation of apaf promoter driven expression cassettes for the production of cysteine-rich, cationic, APs in differentPenicillium species. The system is a perfect tool for the generation of correctly folded proteins with high quality for structure–function analyses.